Administrative leadership styles and their role in achieving administrative creativity in organizations. - HARAN, Elarbi; ZERKOT, Boulerbah (Social Sciences Journal)
The progress and prosperity of organizations depends on its human resources with the intellectual skills and creative abilities on the one hand,And to the leaders of distinguished administrators have the ability to invest these abilities and skills and providing support to the other. This is achieved through the influence of leadership on the behavior of others and from the development of their creative abilities through dialogue and encouraging them to face the difficulties they face while carrying out their duties.If leadership is the ability to influence others by influencing their behavior and that enable the commander of guiding them the right direction to achieve the agreed objectives in the light of good human relationships between the leader and his followers.And it is required elements: the leader and the group’s goals and impact strength and coordination.And from which they can make the individuals working in the creative organization